Fine Granularity Scalability Encryption of MPEG-4 FGS Bitstreams - Zhu, Bin Benjamin; Yang, Yang; Chen, Chang Wen; Li, Shipeng (IEEE Int. Workshop Multimedia Signal Processing (MMSP) 2005, 2005)
In this paper, we propose an encryption scheme for MPEG-4 FGS which provides the same or a little coarser granularity of scalability after encryption. The scheme encrypts compressed data of each video packet or block independently. Initialization vectors are generated with a method to minimize the overhead. The scalability provided in an encrypted codestream using this scheme enables intermediate nodes to truncate an encrypted bitstream at near R-D optimality directly without decryption, which enhances system security. The scheme has virtually negligible overhead, and produces encrypted codestream with virtually the same error resilience performance as the unencrypted case. These features are very desirable in many applications.